An Analysis of Students’ Perceptions Toward Teachers’ Personalities in SMK Telkom 2 Medan - Roy Dedi Ansarika (English Language Teaching Prima Journal (ELT), 2021)
Qualified instructors should have skill in completing their obligations, the planned capabilities are the capacities had to complete errands or occupations in light of information, abilities, perspectives, and characters that are as per foreordained guidelines. Instructors are likewise expected to have character abilities in understanding with Permendiknas number 16 of 2007 concerning character guidelines for teachers in SMK Telkom 2 Medan. This study intends to decide the skill of teachers in SMK Telkom 2 Medan. This research is a descriptive qualitative review, the strategy for gathering information involving a survey as an instrument to get character skill information of grade teachers. The result showed that all the competencies are quite good Keywords: Teachers, Personality, qualified teachers